Regional Development Policy and Regional Inequality - DONALDSON, John A. (Institutional Knowledge at Singapore Management University, 2015)
There can be no Communism with pauperism, or Socialism with pauperism. So to get rich is no sin. However, what we mean by getting rich is different from what you mean. Wealth in a socialist society belongs to the people. To get rich in a socialist society means prosperity for the entire people. The principles of socialism are: first, development of production and second, common prosperity. We permit some people and some regions to become prosperous first, for the purposes of achieving common prosperity faster. That is why our policy will not lead to polarization, to a situation where the rich get richer while the poor get poorer. (Deng Xiaoping in a 1986 US television interview, cited in Fenby 2013) What has caused China’s varying patterns of regional development since the establishment of the People’s Republic of China in 1949? To what extent can central and subnational regional development policies explain the varied patterns of regional development? This chapter reviews the scholarly debate that is key to understanding the prospects for China’s continued development and stability. Although most scholars agree that some variation in the pace of regional development is inevitable and to a certain extent beneficial, the inequality experienced during most of the reform period has been disconcertingly high. This has resulted in dissatisfaction and even protests among those left out of China’s development.